Transformation of Islamic Education Learning Based on Artificial Intelligence to Improve Digital Literacy and Modern Santri Character - Dewi Kurniawati; Anisa Juliana; Tasa Gustina; Nurul Maftukhah; Rahma Wulandari (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
The rapid development of Artificial Intelligence (AI) has transformed learning systems, including Islamic education, by creating opportunities to enhance digital literacy while maintaining students' moral and religious character. This study aims to analyze the transformation of AI-based Islamic education learning, examine the role of AI in strengthening the digital literacy of modern santri, and formulate a learning model that integrates AI with Islamic character education. This research employed a qualitative approach using a library research design. Data were collected from books, scientific journal articles, policy documents, and other relevant academic sources related to artificial intelligence, digital literacy, Islamic education, and character development. Data were analyzed through content analysis using the stages of data condensation, data display, and conclusion drawing. The findings indicate that AI significantly enhances learning effectiveness through personalized instruction, broader access to educational resources, and the development of critical thinking and digital competencies. However, its implementation must remain grounded in Islamic values, with teachers maintaining their essential roles as educators and moral guides. This study proposes the AI Humanistic Islamic Learning Model, which integrates AI utilization, digital literacy, and Islamic character values into a comprehensive learning framework. The model is expected to produce digitally competent, ethically responsible, and morally grounded santri capable of addressing the challenges of the digital era.